The characterization of novel biodegradable blends based on polyhydroxybutyrate - Pankova, Yulia; Shchegolikhin, Alexandr; lordanskii, Alexey; Zhulkina, Anna; Ol'khov, Anatoliy; Zaikov, Gennady (Publishing House of Lviv Polytechnic National University, 2011)
The present paper focuses on the study of novel blends based on poly(3-hydroxybutyrate) (PHB) and polymers with different hydrophilicity (LDPE and PA). Polymer blends were produced from five ratios of PHB/LDPE in order to regulate the resistance to hydrolysis or (bio)degradation through the control of water permeability. The relation between the water transport and morphology (TEM data) shows the impact of polymer component ratio on the regulating water flux in a hydrophobic matrix. To elucidate the role of hydrophilicity of the second component presented in the PHB blends, we studied the PHB/PA blends where PA is the polyamide resin composed of statistical copolymer of hexamethyleneadipinate and e-caprolactam in the ratio of 1:1. The complex of techniques including DCS and FTIR-imaging (for T-scale) demonstrates the interaction between PHB and PA in the temperature ranges of crystallization and melting. The general approach based on Flory-Huggins equation is presented as the way for choosing the pairs of compatible or partly compatible polymers. Вивчено нові полімерні суміші на основі полі(З-гідроксибутирату) (ПГБ) і полімерів з різною гідрофіль¬ністю (ПЕНП і ПА). Для контролювання інтенсивності гідролізу і біодеградації приготовлено композиції ПГБ-ПЕНП з різним співвідношенням компонентів і досліджено проникність води для кожного складу суміші. Встановлено вплив гідрофобного компоненту на потік води у суміші, виходячи із зв 'язку між транспортуванням води і морфологією плівок. З використанням ДСК і Фур'є-спектроскопії вивчено вплив більш гідрофільного компоненту (поліаміду 54С - статичного кополімеру гексаметиленадипінату з є- капролактамом 1:1) на термофізичні властивості суміші (топлення і кристалізація). За допомогою модифікованого рівняння Флорі-Хаггінса встановлено можливість проводити вибір потенційних полімерних компонентів, здатних утворювати сумісні або частково сумісні композиції.
Характеристика новітніх біодеградабельних сумішей на основі полігідроксибутирату
Keywords: polyhydroxybutyrate; biodegradation; polymer blends; thermophysical properties; kinetics; water diffusion; полігідроксибутират; біодеградація; полімерні суміші; термофізичні властивості; кінетика; дифузія води